Sphingosine Kinase 1 Signaling in Breast Cancer: A Potential Target to Tackle Breast Cancer Stem Cells - Hii, Ling-Wei; Chung, Felicia Fei-Lei; Mai, Chun-Wai; Ng, Pei Yuen; Leong, Chee-Onn (Frontiers in Molecular Biosciences, 2021)
Sphingosine kinases (SPHKs) are conserved lipid enzymes that catalyze the formation of sphingo-sine-1-phosphate (S1P) through ATP-dependent phosphorylation of sphingosine. Two distinct SPHK isoforms, namely SPHK1 and SPHK2, have been identified to date, and the former has been implicated for its oncogenic roles in cancer development and progression. While SPHK1 signaling axis has been extensively studied in non-stem breast cancer cells, recent evidence has emerged to suggest a role of SPHK1 in regulating cancer stem cells (CSCs). With the clinical implications of CSCs in disease relapse and metastasis, it is believed that therapeutic approaches that can eradicate both non-stem cancer cells and CSCs could be a key to cancer cure. In this review, we first explore the oncogenic functions of sphingosine kinase 1 in human cancers and summarize current research findings of SPHK1 signaling with a focus on breast cancer. We also discuss the therapeutic potentials and perspectives of targeting SPHK1 signaling in breast cancer and cancer stem cells. We aim to offer new insights and inspire future studies looking further into the regulatory functions of SPHK1 in CSC-driven tumorigenesis, uncovering novel therapeutic avenues of using SPHK1-targeted therapy in the treatment of CSC-enriched refractory cancers.